Improved Chiral Separation of (R,S)-Goitrin by SFC: An Application in Traditional Chinese Medicine - Lixing Nie; Zhong Dai; Shuangcheng Ma (Journal of Analytical Methods in Chemistry)
Like chemical drugs, research and development of herbal medicine also have a need to resolve enantiomers. To help illustrating the antiviral bioactivity of Isatidis Radix, a widely used traditional Chinese medicine (TCM), supercritical fluid chromatography (SFC) was used for analytical and preparative separation of (R,S)-goitrin, which was reported as the active ingredient of the herbal. Improved resolution was achieved on Chiralpak IC column, using acetonitrile as the organic modifier, representing a tenfold increase in speed, compared to the previous normal phase HPLC (NPLC) method. The newly developed chromatographic method was validated in terms of linearity, precision, limit of detection (LOD), and limit of quantitation (LOQ). Scale-up purification of (R)-goitrin and (S)-goitrin was performed on a preparative column with >90% total recovery. The absolute stereochemical assignment of the purified isomers was determined through optical rotation study. This attempt explored SFC’s application in chiral research of traditional Chinese medicine.